Fingerprinting‐based metabolomic approach with LC‐MS to sleep apnea and hypopnea syndrome: A pilot study. Issue 19 (16th August 2013) - Ferrarini, Alessia; Rupérez, Francisco J.; Erazo, Marcela; Martínez, Ma Paz; Villar‐Álvarez, Felipe; Peces‐Barba, Germán; González‐Mangado, Nicolás; Troncoso, María F.; Ruiz‐Cabello, Jesús; Barbas, Coral; Arribas, Coral Barbas
<x xml:space="preserve">Abstract</x> Sleep apnea and hypopnea syndrome (SAHS) is a multicomponent disorder, with associated cardiovascular and metabolic alterations, second in order of frequency among respiratory disorders. Sleep apnea is diagnosed with an overnight sleep test called a polysomnogram, which requires having the patient in hospital. In addition, a more clear classification of patients according to mild and severe presentations would be desirable. The aim of the present study was to assess the relative metabolic changes in SAHS to identify new potential biomarkers for diagnosis, able to evaluate disease severity to establish response to therapeutic interventions and outcomes. For this purpose, metabolic fingerprinting represents a valuable strategy to monitor, in a nontargeted manner, the changes that are at the base of the pathophysiological mechanism of SAHS. Plasma samples of 33 SAHS patients were collected after polysomnography and analyzed with LC coupled to MS (LC‐QTOF‐MS). After data treatment and statistical analysis, signals differentiating nonsevere and severe patients were detected. Putative identification of 14 statistically significant features was obtained and changes that can be related to the episodes of hypoxia/reoxygenation (inflammation) have been highlighted. Among them, the patterns of variation of platelet activating factor and lysophospholipids, together with some compounds related to differential activity of the gut microflora (bile pigments and pipecolic acid) open new lines of research that will benefit our understanding of the alterations, offering new possibilities for adequate monitoring of the stage of the disease.